Climate and seasonality drive the richness and composition of tropical fungal endophytes at a landscape scale - Shuzo Oita (Nature Portfolio, 2021)
Oita, Arnold and colleagues investigate the interplay between abiotic and biotic factors in lowland forest microbial communities. Their results indicate that endophyte richness negatively correlates with temperature seasonality. Both biotic and abiotic factors should be considered when studying endophyte community diversity drivers.